Implementasi Manajemen Penyimpanan Arsip Perpustakaan Secara Elektronik di Sekolah Menengah Kejuruan Negeri 4 Pekanbaru - Putritar Yulia; Akhyar , Yundri (Journal of Sustainable Education, 2024)
This research aims to describe the implementation of electronic library archive storage management at State Vocational School 4 Pekanbaru. This research is a qualitative descriptive research. The subjects of this research were the head of the library as the main informant, the school principal and library staff as supporting informants. This research method is by conducting interviews, observation and documentation. The results of the research show that: 1) Implementation of electronic library archive storage management has four stages, starting from the stages of creation and storage, distribution and use, maintenance and disposition. a) Creation and storage of electronic archives, namely the process of creating archives which are initially in manual form which will be converted into electronic archives. b) This distribution and use uses tools that were originally manual and become electronic with the help of technology and internet networks and supporting equipment. c) Maintenance of electronic archives is carried out by backing up data and periodically checking existing archive data. d) Disposition is the final stage in electronic records which determines whether these records will be retained or will be destroyed. 2) Factors that influence the implementation of electronic library archive storage management. The advantages of using electronic archives are that they take up time, space and energy to work, while the disadvantages are network problems, inadequate facilities and infrastructure.